Compound containing nitrogen heterocyclic ring and siloxane structure, photosensitive resin composition as well as preparation method and application of photosensitive resin composition

By introducing nitrogen-containing heterocycles and siloxane structural compounds into the photosensitive resin composition, the problems of reduced adhesion, high dielectric constant and discoloration of the copper substrate in semiconductor packaging are solved, achieving higher adhesion. and lower dielectric constant, improving the reliability of the material.

CN119350380AActive Publication Date: 2025-01-24POME TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411280380.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-24
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

The existing photosensitive polyimide (PSPI) materials have problems such as decreasing adhesion, high dielectric constant and discoloration of copper substrates in semiconductor packaging, making it difficult to meet the low dielectric constant and high reliability of next-generation semiconductor packaging materials. Sexual needs.

Method used

Introduce the nitrogen -containing rings and silicide structured compounds to the sensitivity resin composition, inhibit the discoloration of copper substrate through complexing reactions, improve the adhesion of the resin layer and substrate, and reduce the medium constant of the curing membrane.

Benefits of technology

It effectively suppresses the discoloration of the copper or copper alloy substrate after development, significantly improves the adhesion between the cured film and the copper or copper alloy substrate, reduces the dielectric constant of the cured film, and improves the overall performance and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350380A_ABST
    Figure CN119350380A_ABST
Patent Text Reader

Abstract

The invention discloses a compound containing a nitrogen heterocyclic ring and a siloxane structure, a photosensitive resin composition and a preparation method and application of the photosensitive resin composition. The compound containing the nitrogen heterocyclic ring and the siloxane structure has a structure as shown in a formula I. The compound has the nitrogen heterocyclic ring and the siloxane structure at the same time, by introducing the compound into the photosensitive resin composition, discoloration of a copper or copper alloy base material after development can be effectively inhibited, meanwhile, the adhesiveness of a cured film and the copper or copper alloy base material is remarkably improved, and the curing effect of the cured film on the copper or copper alloy base material is improved. The dielectric constant of the cured film can be reduced, so that the overall performance of the cured film is improved, and the reliability is higher; # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a nitrogen-containing heterocyclic and siloxane structure compound, a photosensitive resin composition, and a preparation method and application thereof, and belongs to the technical field of functional polymer materials. Background Art

[0002] Photosensitive polyimide (PSPI) is a type of polymer composite material with excellent thermal, mechanical, electrical and chemical properties and photosensitivity. After ultraviolet exposure and development, a three-dimensional pattern with a fine structure is obtained, which significantly simplifies the photolithography process and is an ideal insulating material in the field of microelectronics and semiconductor packaging. With the lightweight, high-performance and multifunctional electronic products, higher requirements are placed on PSPI packaging materials.

[0003] With the development of semiconductor device integration and chip size miniaturization, the wiring mode and installation method of semiconductor devices have changed. The previous gold or aluminum wiring has been changed to copper or copper alloy wiring with lower resistance, and the previous lead-tin eutectic welding has been changed to a ball grid array and chip size installation with higher density installation. Since some active groups in the photosensitive resin composition are easy to react with copper or copper alloy, the copper ions on the surface of the substrate will diffuse into the coating, causing the substrate to discolor, thereby affecting the dielectric properties; the copper ions diffused into the coating will cause the resin and other components to oxidize and decompose during thermal curing, resulting in gaps between the coating and the substrate, and the adhesion is reduced, thereby affecting the reliability of the device. Since the cured resin film is in direct contact with the copper or copper alloy and the solder bump, this requires that the cured film has excellent adhesion to the copper or copper alloy substrate. In addition, the dielectric constant of the traditional PSPI material is high (usually greater than 3), which is difficult to meet the performance requirements of low dielectric constant and low dielectric loss of the next generation of semiconductor packaging materials, and it needs to be modified to low dielectric. Summary of the invention

[0004] In order to solve the above problems, the present application provides a nitrogen-containing heterocycle and siloxane structure compound, which has both a nitrogen heterocycle and a siloxane structure. By introducing the compound into a photosensitive resin composition, the discoloration of the copper or copper alloy substrate after development can be effectively inhibited, while significantly improving the adhesion between the cured film and the copper or copper alloy substrate, and the dielectric constant of the cured film can also be reduced.

[0005] According to the first aspect of the present application, a nitrogen-containing heterocyclic ring and a siloxane structure compound is provided, wherein the nitrogen-containing heterocyclic ring and a siloxane structure compound has a structure shown in Formula I:

[0006]

[0007] In Formula I, W is independently selected from one of the groups shown in Formula II-a;

[0008]

[0009] The dotted lines indicate the connection sites.

[0010] Optionally, the nitrogen-containing heterocyclic and siloxane structure compounds are selected from at least one of the structures shown in Formula I-1, Formula I-2, Formula I-3, Formula I-4, Formula I-5, Formula I-6, Formula I-7, and Formula I-8;

[0011]

[0012]

[0013] According to the second aspect of the present application, a method for preparing the above-mentioned nitrogen-containing heterocyclic and siloxane structure compound is provided, the preparation method comprising:

[0014] Under nitrogen protection, a mixture of 1,3-bis(3-aminopropyl)tetramethyldisiloxane, an acyl chloride compound containing a nitrogen heterocyclic structure, a catalyst and a solvent is reacted to obtain a compound containing a nitrogen heterocyclic structure and a siloxane structure.

[0015] Optionally, the acyl chloride compound having a nitrogen-containing heterocyclic structure is selected from at least one of the structures shown in Formula II-b;

[0016]

[0017] Optionally, the molar ratio of the 1,3-bis(3-aminopropyl)tetramethyldisiloxane to the acyl chloride compound having a nitrogen-containing heterocyclic structure is 1:2 to 2.5.

[0018] Optionally, the molar ratio of the 1,3-bis(3-aminopropyl)tetramethyldisiloxane to the catalyst is 1:1-3.

[0019] Optionally, the catalyst is selected from triethylamine and / or pyridine.

[0020] Optionally, the solvent is selected from at least one of tetrahydrofuran, dimethyl sulfoxide, propylene glycol monomethyl ether and toluene.

[0021] Optionally, the preparation method comprises:

[0022] A mixed solution containing a solvent, a catalyst and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is added dropwise to a solution of an acyl chloride compound containing a nitrogen heterocyclic structure to react and obtain a compound containing a nitrogen heterocyclic structure and a siloxane structure.

[0023] Optionally, during the dropwise addition, the temperature of the reaction system is controlled to be -10°C to 10°C, and after the dropwise addition is completed, the reaction is continued at 25±2°C for 5 to 8 hours.

[0024] Optionally, the temperature of the reaction system during the dropwise addition process is independently selected from any value among -10°C, -8°C, -6°C, -4°C, -2°C, 0°C, 2°C, 4°C, 6°C, 8°C, 10°C or a range between any two of the above.

[0025] Optionally, the reaction conditions are: the temperature is controlled at -10°C to 10°C during the dropwise addition, and the reaction is continued at 25°C for 5 to 8 hours after the dropwise addition is completed; after the reaction is completed, the triethylamine salt is filtered out, and the filtrate is evaporated under reduced pressure to remove residual triethylamine (pyridine), solvent, generated hydrochloric acid and other substances to obtain purified nitrogen-containing heterocyclic and siloxane structure compounds.

[0026] According to a third aspect of the present application, a photosensitive resin composition is provided, wherein the photosensitive resin composition is obtained by uniformly mixing raw materials containing a polyimide precursor resin, a nitrogen-containing heterocyclic compound and a siloxane structure compound, a photoinitiator, a crosslinking agent, and a solvent I;

[0027] The nitrogen-containing heterocyclic ring and siloxane structure compound is selected from the nitrogen-containing heterocyclic ring and siloxane structure compound described above.

[0028] Optionally, the polyimide precursor resin is polyamic acid or polyamic acid ester, having a structure shown in Formula III:

[0029]

[0030] In formula III, A is a tetravalent organic group having 2 to 16 carbon atoms; B is a divalent organic group having 2 to 20 carbon atoms;

[0031] n is an integer from 2 to 200;

[0032] R 1 , R 2 One independently selected from a hydrogen atom, a monovalent organic group having a structure represented by formula IV, and a saturated aliphatic group having 1 to 4 carbon atoms;

[0033]

[0034] In Formula IV, R 3 , R 4 , R 5 They are independently selected from hydrogen atoms or organic groups having 1 to 3 carbon atoms, m is an integer of 2 to 10, and * represents an insertion site.

[0035] Optionally, R 3 , R 4 From the viewpoint of photosensitivity, hydrogen atoms are preferred. 5 Preferred is a hydrogen atom or a methyl group.

[0036] Alternatively, m is preferably an integer of 2 to 4 from the viewpoint of photosensitivity.

[0037] Optionally, in the polyimide precursor resin of the structure shown in Formula III, A is derived from aromatic tetracarboxylic dianhydride.

[0038] Optionally, the aromatic tetracarboxylic dianhydride is selected from at least one of pyromellitic dianhydride, 4,4'-oxydiphthalic anhydride, biphenyl-3,3',4,4'-tetracarboxylic dianhydride, benzophenone-3,3',4,4'-tetracarboxylic dianhydride, diphenyl sulfone-3,3',4,4'-tetracarboxylic dianhydride, diphenylmethane-3,3',4,4'-tetracarboxylic dianhydride, 2,2-bis(3,4-phthalic anhydride)propane, and 2,2-bis(3,4-phthalic anhydride)-1,1,1,3,3,3-hexafluoropropane.

[0039] Optionally, in the polyimide precursor resin of the structure represented by Formula III, B is derived from an aromatic diamine.

[0040] Optionally, the aromatic diamine is selected from p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminobiphenyl, 3,4'-diaminobiphenyl, 3,3'-diaminobiphenyl, 4,4'-diaminobenzophenone, 3 , 4'-diaminobenzophenone, 3,3'-diaminobenzophenone, 4,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 2,2-bis(4-aminophenyl)benzene, 1,4-bis(3-aminopropyldimethylsilyl)benzene, 4,4'-diamino-2,2'-dimethylbicyclohexane.

[0041] Optionally, the compound of the structure represented by formula IV is derived from alcohols having an unsaturated double bond.

[0042] Optionally, the alcohol with unsaturated double bonds is selected from hydroxyethyl acrylate, hydroxyethyl methacrylate, 2-acryloxyethanol, 1-acryloxy-3-propanol, 2-acrylamideethanol, hydroxymethyl vinyl ketone, 2-hydroxyethyl vinyl ketone, 2-hydroxy-3-methoxypropyl acrylate, 2-hydroxy-3-butoxypropyl acrylate, 2-hydroxy-3-phenoxypropyl acrylate, 2-hydroxy-3-cyclohexyloxypropyl acrylate, 2-hydroxy-3-tert-butoxypropyl acrylate, 2-methyl At least one of acryloyloxyethanol, 1-methacryloyloxy-3-propanol, 2-methacrylamideethanol, hydroxymethyl vinyl ketone, 2-hydroxyethyl vinyl ketone, 2-hydroxy-3-methoxypropyl methacrylate, 2-hydroxy-3-butoxypropyl methacrylate, 2-hydroxy-3-phenoxypropyl methacrylate, 2-hydroxy-3-butoxypropyl methacrylate, 2-hydroxy-3-tert-butoxypropyl methacrylate, and 2-hydroxy-3-cyclohexyloxypropyl methacrylate.

[0043] Optionally, the preparation method of the polyamic acid ester is as follows: firstly, an aromatic tetracarboxylic dianhydride is reacted with an alcohol compound containing an unsaturated double bond to form a diacid diester, and then the diacid diester is subjected to a condensation reaction with an aromatic diamine solution to form a polyamic acid ester solution.

[0044] After the amide polycondensation reaction is completed, the by-product of the dehydration condensation agent in the reaction solution is filtered out as needed, and the reaction solution is put into a poor solvent such as water, aliphatic lower alcohol, or a mixture thereof to precipitate a polymer. The polymer is purified by repeating operations such as redissolution and reprecipitation as needed, and then vacuum dried to obtain a polyamic acid ester resin.

[0045] From the perspective of heat resistance and mechanical properties after heat treatment, the weight average molecular weight (Mw) of the above resin is 20000 to 30000. The weight average molecular weight (Mw) of the resin is measured by gel permeation chromatography (the instrument model is LC-20AD of Shimadzu Corporation, Japan) by standard polystyrene conversion, and the elution solvent is N-methylpyrrolidone.

[0046] Optionally, the mass ratio of the polyimide precursor resin to the nitrogen-containing heterocyclic and siloxane structure compound is 100:0.1-20.

[0047] Optionally, the mass ratio of the polyimide precursor resin to the nitrogen-containing heterocyclic and siloxane structure compound is 100:1-10.

[0048] Optionally, the mass ratio of the polyimide precursor resin to the photoinitiator is 100:0.1-30.

[0049] Optionally, the mass ratio of the polyimide precursor resin to the cross-linking agent is 100:0.1-30.

[0050] Optionally, the mass ratio of the polyimide precursor resin to the solvent I is 100:80-2000.

[0051] Optionally, the mass ratio of the polyimide precursor resin to the solvent I is independently selected from any value among 80:100, 100:100, 100:150, 100:200, 100:250, 100:300, 100:350, 100:400, 100:500, 100:600, 100:700, 100:800, 100:900, 100:1000, 100:1500, 100:2000 or a range value between any two of the above.

[0052] Preferably, the mass ratio of the polyimide precursor resin to the solvent I is 100:100-1000.

[0053] More preferably, the mass ratio of the polyimide precursor resin to the solvent I is 100:150-500.

[0054] Optionally, the photoinitiator is selected from at least one of benzophenone compounds, benzyl compounds, coumarin compounds, anthraquinone compounds, benzoin compounds, thioxanthone compounds, thiol compounds, glycine compounds, oxime compounds, α-aminoalkylphenone compounds, 2,2'-bis(o-chlorophenyl)-4,4',5,5'-tetraphenylbiimidazole, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (trade name: BAPO, manufactured by Wuhan Yuancheng Technology).

[0055] Among the above-mentioned initiators, oxime compounds are preferred from the viewpoint of photosensitivity.

[0056] Optionally, the oxime compound is selected from at least one of 1-phenyl-1,2-butanedione-2-(o-methoxycarbonyl) oxime, 1-phenyl-1,2-propanedione-2-(o-methoxycarbonyl) oxime, 1-phenyl-1,2-propanedione-2-(o-ethoxycarbonyl) oxime, 1-phenyl-1,2-propanedione-2-(o-benzoyl) oxime, 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-(O-benzoyl oxime) (trade name: OXE-01, manufactured by BASF), and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(0-acetyl oxime) (trade name: OXE-02, manufactured by BASF).

[0057] Optionally, the cross-linking agent undergoes polymerization reaction with the resin and the same molecules to form a cross-linked network structure, which can improve the heat resistance and chemical resistance of the cured film formed by the photosensitive resin composition.

[0058] Optionally, the crosslinking agent is selected from tetraethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, trimethylolpropane diacrylate, trimethylolpropane triacrylate, trimethylolpropane dimethacrylate, etc., but is not limited to these. The above crosslinking agents can be used alone or in combination of two or more.

[0059] Optionally, the solvent I is selected from at least one of N-methylpyrrolidone, methyl ethyl ketone, acetone, γ-butyrolactone, ethyl acetate, ethyl lactate, toluene, xylene, diethylene glycol monobutyl ether, propylene glycol methyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, tetrahydrofuran, dioxane, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.

[0060] Furthermore, in order to improve the stability of the photosensitive resin composition, the photosensitive resin composition may further include a polymerization inhibitor.

[0061] Optionally, the inhibitor includes at least one of hydroquinone, p-hydroxyanisole, N-nitrosodiphenylamine, phenothiazine, p-tert-butylcatechol, N-phenylnaphthylamine, ethylenediaminetetraacetic acid, 1,2-cyclohexanediaminetetraacetic acid, 2,6-di-tert-butyl-p-methylphenol, 5-nitroso-8-hydroxyquinoline, and N-nitroso-N(1-naphthyl)hydroxylamine ammonium salt.

[0062] Optionally, the mass ratio of the polyimide precursor resin to the polymerization inhibitor is 100:0.1-10.

[0063] Optionally, the mass ratio of the polyimide precursor resin to the inhibitor is independently selected from any value of 100:0.1, 100:0.3, 100:0.5, 100:0.8, 100:1, 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10 or a range between any two of the above.

[0064] Preferably, the mass ratio of the polyimide precursor resin to the polymerization inhibitor is 100:0.5-5.

[0065] According to a fourth aspect of the present application, a method for preparing a photosensitive resin composition is provided, comprising: dissolving and dispersing each component uniformly, and then filtering to obtain the photosensitive resin composition.

[0066] In one embodiment, the preparation method of the photosensitive resin composition includes: adding a polyimide precursor resin, an inhibitor, and a solvent into a three-necked flask, stirring until completely dissolved, adding a photoinitiator and a cross-linking agent in sequence, and continuing to stir until completely dispersed; and filtering using a 1 μm polytetrafluoroethylene filter membrane to obtain a photosensitive resin composition.

[0067] According to a fifth aspect of the present application, a polyimide film is provided, wherein the polyimide film is obtained by coating and curing a photosensitive resin composition;

[0068] The photosensitive resin composition is selected from the photosensitive resin composition described above.

[0069] In the preparation process of the polyimide film in this application, the substrate to be coated is not particularly limited, and those skilled in the art can make conventional selections, including silicon wafers, aluminum wafers, silver wafers, copper wafers, copper alloy wafers, ceramic wafers, etc. The specific coating method is also not particularly limited, and examples include spray coating, spin coating, and ink scraper method. In the actual coating operation process, the film thickness will also be different due to different coating methods, rotation speeds, viscosities, and composition components. The coating method is preferably spin coating.

[0070] Optionally, the polyimide film has a cured relief pattern.

[0071] Optionally, the method for preparing the polyimide film having a cured relief pattern comprises: coating a photosensitive resin composition on a substrate, followed by drying, exposing, developing, and curing to obtain a polyimide film.

[0072] In the preparation process of the polyimide film with a solidified relief pattern in the present application, the drying method can be a baking operation, specifically, baking can be performed in an oven, a heating table, an infrared lamp, etc., preferably a heating table baking. More preferably, the drying temperature is 80 to 150°C, and the drying time is 1 to 10 minutes. More preferably, the drying temperature is 100 to 130°C, and the drying time is 2 to 5 minutes. After the drying operation is completed, the thickness of the photosensitive resin film layer is measured after naturally cooling to 25°C.

[0073] In the preparation process of the polyimide film with a cured relief pattern in the present application, the specific exposure operation is to use an exposure device to expose the above-formed resin film through a mask with a pattern through the dried photosensitive resin film layer. Common active light rays include ultraviolet rays, X-rays, electron beams, etc. In the present invention, a mercury lamp is preferably used for exposure, which includes three light sources: i-line (365nm), h-line (405nm), and g-line (436nm).

[0074] In the preparation method of the above-mentioned polyimide film, a pattern is formed by removing the unexposed part using a developer. Common developers include: N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, methanol, ethanol, isopropanol, ethyl lactate, butyl acetate, propylene glycol monomethyl ether acetate, cyclopentanone, cyclohexanone, isobutyl ketone, tetramethylammonium hydroxide aqueous solution, etc. After development, it is preferably rinsed with deionized water, ethanol, isopropanol, ethyl lactate, propylene glycol monomethyl ether acetate, etc. For example, a developer and a rinse solution are poured into two glass culture dishes respectively. The developer temperature is controlled to be 25±1°C, the exposed resin film is immersed in the developer, and the timing is started immediately. After the unexposed part is completely exposed to the substrate, the development is completed, the timing is stopped, and the time required for the whole process is recorded.

[0075] In the above-mentioned method for preparing the polyimide film, the temperature of the curing operation is 300-400°C, preferably 350°C. The pattern obtained after development and rinsing is thermally imidized to convert it into a cured film. The heating treatment usually selects staged heating, and maintains a certain time at different temperatures or selects a certain temperature range for continuous heating. For example, a heat treatment method of 30 minutes at 150°C, 250°C, and 350°C, or a method of continuously heating from room temperature to 350°C. Inert gases such as nitrogen and argon are often used during curing. As a specific application example, first control the oxygen content in the oven cavity to be reduced to below 50ppm, then start heating to 150°C and keep the temperature constant for 30 minutes, then heat to 250°C and keep the temperature constant for 30 minutes, then heat to 350°C and keep the temperature constant for 1 hour, cool to room temperature, and finally obtain a cured relief pattern.

[0076] According to a sixth aspect of the present application, there is provided an application of the polyimide film described above in a semiconductor element.

[0077] The semiconductor element described in the present application preferably includes a polyimide film having a cured relief pattern.

[0078] The present application provides a compound having both a nitrogen heterocycle and a siloxane structure. By introducing the compound into a photosensitive resin composition, the discoloration of a copper or copper alloy substrate after development can be effectively suppressed, while the adhesion between a cured film and the copper or copper alloy substrate can be significantly improved, and the dielectric constant of the cured film can be reduced, thereby improving the overall performance of the cured film and making it more reliable.

[0079] The beneficial effects of this application include:

[0080] The compound provided in the present application has both nitrogen heterocyclic and siloxane structures, wherein the nitrogen heterocyclic group reacts with the copper or copper alloy substrate to form a stable complex, protects the substrate from being corroded by the photosensitive resin composition, inhibits the discoloration of the copper or copper alloy substrate, and enhances the adhesion between the resin layer and the substrate; the presence of the siloxane structure further improves the adhesion between the cured film and the substrate. By introducing the compound into the photosensitive resin composition, the discoloration of the copper or copper alloy substrate after the development of the photosensitive resin composition can be effectively inhibited, and the adhesion between the cured film and the copper or copper alloy substrate can be significantly improved. In addition, the dielectric constant of the cured film can be reduced, so that the overall performance of the cured film is improved, and the reliability is higher. BRIEF DESCRIPTION OF THE DRAWINGS

[0081] Figure 1 This is a diagram showing the degree of discoloration of the copper or copper alloy substrate in the examples and comparative examples of the present application. DETAILED DESCRIPTION

[0082] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0083] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0084] The structural formulas and names of the raw materials P-1, P-2, P-3, P-4, P-5, P-6, P-7, and P-8 involved below are shown in Table 1.

[0085] Table 1

[0086]

[0087]

[0088] Characterization of compounds in this application

[0089] (1) Infrared test

[0090] The synthesized compounds were tested using a Fourier transform infrared spectrometer (Tensor-27, Bruker, Germany) to detect whether the compounds in this application were successfully prepared. If the spectrum shows: 1640 cm -1 ~1660cm -1 The vibration absorption peak of the C=O bond of -CONH appears at 1540 cm -1 ~1550 cm -1 If the vibration absorption peak of the CN bond of -CONH appears at , it can be proved that the compound of the present application is successfully synthesized.

[0091] (2) MRI test

[0092] The Bruker 400 nuclear magnetic resonance instrument was used to test the compounds of the present application.1 The characterization was carried out in H spectroscopy mode (TMS was used as the internal standard and DMSO was used as the solvent).

[0093] Preparation Example 1 Preparation of Compound I-1

[0094] Under a dry nitrogen flow, 32.32 g (0.2 mol) of P-1 and 100 g of tetrahydrofuran (hereinafter referred to as THF) solvent were added to a 500 ml four-necked flask equipped with a tetrafluoroethylene stirring paddle, a thermometer and a constant pressure dropping funnel. The mixture was stirred at room temperature until completely dissolved, and the mixture was cooled to below 0°C in an ice bath. A mixed solution of 24.85 g (0.1 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 20.22 g (0.2 mol) of triethylamine and 80 g of THF solvent was slowly added dropwise. The system temperature was controlled at -10°C to 10°C. After the addition was completed, the temperature was raised to 25°C and the reaction was continued for 8 h. After the reaction was completed, the triethylamine hydrochloride was filtered and the filtrate was distilled under reduced pressure to remove residual triethylamine, hydrochloric acid and solvent to obtain purified compound I-1.

[0095]

[0096] The infrared spectrum information of compound I-1 is as follows:

[0097] FT-IR:1648cm -1 It is the C=O symmetric stretching vibration of -CONH, 1550cm -1 It is the CN asymmetric stretching vibration of -CONH.

[0098] The H NMR spectrum information of compound I-1 is as follows:

[0099] 1 HNMR(DMSO): δ: 0.22(s,12H),0.61(t,4H),1.51(m,4H),2.5(s,2H),3.42(t,4H),3.75(s,8H),4.25(s,4H),8.01(s,2H),8.69(s,2H).

[0100] Preparation Example 2 Preparation of Compound I-2

[0101] Under a dry nitrogen flow, 29.71 g (0.2 mol) of P-2 and 100 g of tetrahydrofuran (hereinafter referred to as THF) solvent were added to a 500 ml four-necked flask equipped with a tetrafluoroethylene stirring paddle, a thermometer, and a constant pressure dropping funnel. The mixture was stirred at room temperature until completely dissolved, and the mixture was cooled to below 0°C in an ice bath. A mixed solution of 24.85 g (0.1 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 20.22 g (0.2 mol) of triethylamine, and 80 g of THF solvent was slowly added dropwise. The system temperature was controlled at -10°C to 10°C. After the addition was completed, the temperature was raised to 25°C, and the reaction was continued for 8 h. After the reaction was completed, the triethylamine hydrochloride was filtered, and the filtrate was distilled under reduced pressure to remove residual triethylamine, hydrochloric acid, and solvent to obtain purified compound I-2.

[0102]

[0103] The infrared spectrum information of compound I-2 is as follows:

[0104] FT-IR:1645cm -1 It is the C=O symmetric stretching vibration of -CONH, 1548cm -1 It is the CN asymmetric stretching vibration of -CONH.

[0105] The H NMR spectrum information of compound I-2 is as follows:

[0106] 1 HNMR (DMSO): δ: 0.22 (s, 12H), 0.61 (t, 4H), 1.51 (m, 4H), 3.39~3.43 (m, 12H), 6.02 (s, 2H), 10.86 (s, 2H).

[0107] Preparation Example 3 Preparation of Compound I-3

[0108] Under a dry nitrogen flow, 28.51 g (0.2 mol) of P-3 and 100 g of tetrahydrofuran (hereinafter referred to as THF) solvent were added to a 500 ml four-necked flask equipped with a tetrafluoroethylene stirring paddle, a thermometer, and a constant pressure dropping funnel. The mixture was stirred at room temperature until completely dissolved, and the mixture was cooled to below 0°C in an ice bath. A mixed solution of 24.85 g (0.1 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 20.22 g (0.2 mol) of triethylamine, and 80 g of THF solvent was slowly added dropwise. The system temperature was controlled at -10°C to 10°C. After the addition was completed, the temperature was raised to 25°C, and the reaction was continued for 8 h. After the reaction was completed, the triethylamine hydrochloride was filtered, and the filtrate was distilled under reduced pressure to remove residual triethylamine, hydrochloric acid, and solvent to obtain purified compound I-3.

[0109]

[0110] The infrared spectrum information of compound I-3 is as follows:

[0111] FT-IR:1643cm -1 It is the C=O symmetric stretching vibration of -CONH, 1545cm -1 It is the CN asymmetric stretching vibration of -CONH.

[0112] The H NMR spectrum information of compound I-3 is as follows:

[0113] 1 HNMR(DMSO): δ: 0.22(s,12H),0.61(t,4H),1.51(m,4H),3.18(t,4H),8.06(t,2H),8.93(s,2H),9.23(d,4H).

[0114] Preparation Example 4 Preparation of Compound I-4

[0115] Under a dry nitrogen flow, 43.73 g (0.2 mol) of P-4 and 100 g of tetrahydrofuran (hereinafter referred to as THF) solvent were added to a 500 ml four-necked flask equipped with a tetrafluoroethylene stirring paddle, a thermometer, and a constant pressure dropping funnel. The mixture was stirred at room temperature until completely dissolved, and the mixture was cooled to below 0°C in an ice bath. A mixed solution of 24.85 g (0.1 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 20.22 g (0.2 mol) of triethylamine, and 80 g of THF solvent was slowly added dropwise. The system temperature was controlled at -10°C to 10°C. After the addition was completed, the temperature was raised to 25°C, and the reaction was continued for 8 h. After the reaction was completed, the triethylamine hydrochloride was filtered, and the filtrate was distilled under reduced pressure to remove residual triethylamine, hydrochloric acid, and solvent to obtain purified compound I-4.

[0116]

[0117] The infrared spectrum information of compound I-4 is as follows:

[0118] FT-IR:1650cm -1 It is the C=O symmetric stretching vibration of -CONH, 1547cm -1 It is the CN asymmetric stretching vibration of -CONH.

[0119] The H NMR spectrum information of compound I-4 is as follows:

[0120] 1 HNMR(DMSO): δ: 0.22(s,12H),0.61(t,4H),1.55(m,4H),3.43(t,4H),7.22(t,2H),7.95~8.00(m,8H),8.44(s,2H),8.73(d,4H).

[0121] Preparation Example 5 Preparation of Compound I-5

[0122] Under a dry nitrogen flow, 44.32 g (0.2 mol) of P-5 and 100 g of tetrahydrofuran (hereinafter referred to as THF) solvent were added to a 500 ml four-necked flask equipped with a tetrafluoroethylene stirring paddle, a thermometer, and a constant pressure dropping funnel. The mixture was stirred at room temperature until completely dissolved, and the mixture was cooled to below 0°C in an ice bath. A mixed solution of 24.85 g (0.1 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 20.22 g (0.2 mol) of triethylamine, and 80 g of THF solvent was slowly added dropwise. The system temperature was controlled at -10°C to 10°C. After the addition was completed, the temperature was raised to 25°C, and the reaction was continued for 8 h. After the reaction was completed, the triethylamine hydrochloride was filtered, and the filtrate was distilled under reduced pressure to remove residual triethylamine, hydrochloric acid, and solvent to obtain purified compound I-5.

[0123]

[0124] The infrared spectrum information of compound I-5 is as follows:

[0125] FT-IR:1646cm -1 It is the C=O symmetric stretching vibration of -CONH, 1548cm -1 It is the CN asymmetric stretching vibration of -CONH.

[0126] The H NMR spectrum information of compound I-5 is as follows:

[0127] 1 HNMR(DMSO): δ:0.22(s,12H),0.61(t,4H),0.99(d,6H),1.51(m,4H),3.18(t,4H ),3.39(m,2H),3.9(s,2H),7.33(m,2H),7.50(d,4H),7.63(t,4H),8.21(s,2H).

[0128] Preparation Example 6 Preparation of Compound I-6

[0129] Under a dry nitrogen flow, 29.31 g (0.2 mol) of P-6 and 100 g of tetrahydrofuran (hereinafter referred to as THF) solvent were added to a 500 ml four-necked flask equipped with a tetrafluoroethylene stirring paddle, a thermometer, and a constant pressure dropping funnel. The mixture was stirred at room temperature until completely dissolved, and the mixture was cooled to below 0°C in an ice bath. A mixed solution of 24.85 g (0.1 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 20.22 g (0.2 mol) of triethylamine, and 80 g of THF solvent was slowly added dropwise. The system temperature was controlled at -10°C to 10°C. After the addition was completed, the temperature was raised to 25°C, and the reaction was continued for 8 h. After the reaction was completed, the triethylamine hydrochloride was filtered, and the filtrate was distilled under reduced pressure to remove residual triethylamine, hydrochloric acid, and solvent to obtain purified compound I-6.

[0130]

[0131] The infrared information of compound I-6 is as follows:

[0132] FT-IR:1650cm -1 It is the C=O symmetric stretching vibration of -CONH, 1545cm -1 It is the CN asymmetric stretching vibration of CO-NH.

[0133] The H NMR spectrum information of compound I-6 is as follows:

[0134] 1 HNMR(DMSO): δ: 0.22(s,12H),0.61(t,4H),1.51(m,4H),3.43(t,4H),5.60(s,4H),8.01(s,2H),9.45(s,2H).

[0135] Preparation Example 7 Preparation of Compound I-7

[0136] Under a dry nitrogen flow, 48.93 g (0.2 mol) of P-7 and 100 g of tetrahydrofuran (hereinafter referred to as THF) solvent were added to a 500 ml four-necked flask equipped with a tetrafluoroethylene stirring paddle, a thermometer, and a constant pressure dropping funnel. The mixture was stirred at room temperature until completely dissolved, cooled to below 0°C in an ice bath, and a mixed solution of 24.85 g (0.1 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 20.22 g (0.2 mol) of triethylamine, and 80 g of THF solvent was slowly added dropwise. The system temperature was controlled at -10°C to 10°C. After the addition was completed, the temperature was raised to 25°C, and the reaction was continued for 8 hours. After the reaction was completed, the triethylamine hydrochloride was filtered, and the filtrate was distilled under reduced pressure to remove residual triethylamine, hydrochloric acid, and solvent to obtain purified compound I-7.

[0137]

[0138] The infrared spectrum information of compound I-7 is as follows:

[0139] FT-IR:1647cm -1 It is the C=O symmetric stretching vibration of -CONH, 1548cm -1 It is the CN asymmetric stretching vibration of -CONH.

[0140] The H NMR spectrum information of compound I-7 is as follows:

[0141] 1 HNMR(DMSO): δ: 0.22(s,12H),0.61(t,4H),1.55(m,4H),3.43(t,4H),7.95~8.00(m,8H),8.44(s,2H),15.0(s,2H).

[0142] Preparation Example 8 Preparation of Compound I-8

[0143] Under a dry nitrogen flow, 48.34 g (0.2 mol) of P-8 and 100 g of tetrahydrofuran (hereinafter referred to as THF) solvent were added to a 500 ml four-necked flask equipped with a tetrafluoroethylene stirring paddle, a thermometer, and a constant pressure dropping funnel. The mixture was stirred at room temperature until completely dissolved, cooled to below 0°C in an ice bath, and a mixed solution of 24.85 g (0.1 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 20.22 g (0.2 mol) of triethylamine, and 80 g of THF solvent was slowly added dropwise. The system temperature was controlled at -10°C to 10°C. After the addition was completed, the temperature was raised to 25°C, and the reaction was continued for 8 hours. After the reaction was completed, the triethylamine hydrochloride was filtered, and the filtrate was distilled under reduced pressure to remove residual triethylamine, hydrochloric acid, and solvent to obtain purified compound I-8.

[0144]

[0145] The infrared spectrum information of compound I-8 is as follows:

[0146] FT-IR:1649cm -1 It is the C=O symmetric stretching vibration of -CONH, 1550cm -1 It is the CN asymmetric stretching vibration of -CONH.

[0147] The H NMR spectrum information of compound I-8 is as follows:

[0148] 1HNMR(DMSO): δ:0.22(s,12H),0.61(t,4H),1.51(m,4H),3.43(t,4H),4.2 6(s,4H),4.63(s,4H),7.51~7.53(m,4H),8.01~8.02(m,4H),8.18(m,2H).

[0149] Synthesis Example 1 Synthesis of polyimide precursor resin

[0150] 31.02 g (0.1 mol) of 4,4'-oxydiphthalic anhydride (ODPA) was placed in a 500 mL three-necked flask, and 26.03 g (0.2 mol) of hydroxyethyl methacrylate (HEMA) and 100.00 g of γ-butyrolactone (GBL) were added. 15.82 g of pyridine (0.2 mol) was added dropwise at a temperature below 10°C while stirring to obtain a reaction mixture. The temperature was naturally raised to 25°C and stirred for 12 hours.

[0151] Next, under ice bath conditions, the reaction mixture was added to 50.00 g of a GBL solution containing 41.25 g (0.2 mol) of dicyclohexylcarbodiimide (DCC) with stirring for 40 min. Under nitrogen protection, 70.00 g of a GBL solution containing 19.03 g (0.095 mol) of 4,4'-diaminodiphenyl ether (ODA) was added for 60 min. The temperature was naturally raised to 25°C, 80.00 g of GBL was added, and stirring was continued for 12 h. After that, 6.00 g of ethanol was added and stirred for 1 hr. The precipitate produced in the reaction mixture was removed by filtration to obtain a reaction solution.

[0152] The obtained reaction solution was added to 1L of ethanol to precipitate a polymer, and then the precipitated polymer was dissolved in 300mL of tetrahydrofuran. The obtained polymer solution was dropped into 5L of ultrapure water to precipitate a polymer. The obtained precipitate was filtered out and vacuum dried at 50°C for 72h to obtain a polymer powder, i.e., a polyimide precursor resin.

[0153] The weight average molecular weight (Mw) of the resin was measured by gel permeation chromatography (standard polystyrene conversion), and a GPC system of Shimadzu Corporation was used for the measurement. The weight average molecular weight (Mw) of the obtained polyimide precursor resin was 25,000 to 30,000.

[0154] Example 1

[0155] In a three-necked flask equipped with a stirrer, 10.0 g of polyimide precursor resin and 0.1 g of inhibitor p-hydroxyanisole (MEHQ) were dissolved in 20.0 g of N-methylpyrrolidone (NMP), stirred until completely dissolved, 0.5 g of compound I-1, 0.5 g of photoinitiator 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-(O-benzoyloxime) (OXE-01), and 2.0 g of crosslinking agent tetraethylene glycol dimethacrylate (TEGDMA) were added in sequence, and stirring was continued until completely dispersed and uniformly dispersed, and filtered using a 1.0 μm filter membrane to obtain a photosensitive resin composition Q-1, and the viscosity measured at 25°C was 2000-3000 cp. The viscosity of the photosensitive resin composition was tested using a rotational viscometer (Brookfield DV2T RV) at 25±0.1°C.

[0156] Examples 2 to 14, Comparative Example 1

[0157] The preparation method of the photosensitive resin composition is the same as that of Example 1, except that the addition ratio of the compounds in the preparation of the photosensitive resin composition is different, as shown in Table 2.

[0158] Table 2

[0159]

[0160]

[0161] It should be noted that the effect evaluation of the photosensitive resin composition in the examples and comparative examples was carried out according to the following method.

[0162] (1) Copper discoloration test

[0163] The photosensitive resin composition was spin-coated onto a copper or copper alloy substrate, and then soft-baked at 120°C for 3 minutes using a heating table to obtain a photosensitive resin film with a thickness of 10 to 20 μm. After exposure, the film was developed in a developer to completely dissolve the unexposed portion. The discoloration of the copper or copper alloy substrate after development was observed using a 100x optical microscope. Figure 1 As shown in the figure, the discoloration degree of copper or copper alloy substrate is divided into three levels: no discoloration, slight discoloration, and severe discoloration ( Figure 1 The small and medium squares are the photolithography patterns left on the copper substrate after development).

[0164] (2) Adhesion peeling test

[0165] The photosensitive resin composition sample was uniformly coated on a copper or copper alloy substrate using a coating machine, and was placed on a heating table at 120°C for 3 minutes for soft baking to obtain a resin film with a film thickness of 10 to 20 μm. A grid of 10 rows × 10 columns was drawn on the resin film using a gridding machine (BYK-Gardner A-5125), and then the film was placed in a vacuum oxygen-free oven (MOLZK-32D1) for heat treatment: the temperature was initially raised to 150°C and kept constant for 30 minutes, then raised to 250°C and kept constant for 30 minutes, then raised to 350°C and kept constant for 1 hour, and then cooled to room temperature to finally obtain a cured film. The cured film was placed in a PCT test chamber for a 200-hour PCT aging test (121°C, 2 atmospheres of saturated steam; PCT-30, Dongguan Hongjin Technology). After the PCT test was completed, a peeling test was performed using tape (special transparent 3M tape) in accordance with the national standard GB / T 9286-1998 for the cross-cutting test of paint and varnish films. The number of cross-cuttings peeled off was recorded as the peeling condition after the PCT test.

[0166] In the adhesive peeling test, when the number of peeled pieces was less than 5, it was considered "excellent", when it was less than 10, it was considered "good", and when it was greater than or equal to 10, it was considered "poor".

[0167] (3) Dielectric constant

[0168] With reference to the national standard GB / T 31838.6-2021 Dielectric and resistive properties of solid insulating materials Part 6: Dielectric properties (AC method) relative dielectric constant and dielectric loss factor (frequency 0.1Hz~10MHz), the dielectric constant of the cured film was measured at 25°C using a DMS2000 high and low temperature dielectric resistance thermometer, and the value at a frequency of 1MHz was recorded.

[0169] The photosensitive resin composition prepared above was evaluated according to the copper discoloration test, adhesion peeling test, and dielectric property test methods described above. The results are shown in Table 3.

[0170] Table 3

[0171]

[0172]

[0173] It can be seen from the data in Table 3 that the present application provides a compound containing a nitrogen heterocycle and a siloxane structure. By introducing the compound into the photosensitive resin composition, the discoloration of the copper or copper alloy substrate after development can be effectively suppressed, while significantly improving the adhesion between the cured film and the copper or copper alloy substrate, and reducing the dielectric constant of the cured film, thereby improving the overall performance of the cured film and making it more reliable.

[0174] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A nitrogen-containing heterocyclic and siloxane structure compound, characterized in that: The nitrogen-containing heterocyclic and siloxane structure compound has a structure shown in Formula I: In Formula I, W is independently selected from one of the groups shown in Formula II-a; The dotted lines indicate the connection sites.

2. The nitrogen-containing heterocyclic and siloxane structure compound according to claim 1, characterized in that: The nitrogen-containing heterocyclic and siloxane structure compound is selected from at least one of the structures shown in Formula I-1, Formula I-2, Formula I-3, Formula I-4, Formula I-5, Formula I-6, Formula I-7, and Formula I-8; 3. The method for preparing the nitrogen-containing heterocyclic and siloxane structure compound according to any one of claims 1 to 2, characterized in that: The preparation method comprises: Under nitrogen protection, a mixture of 1,3-bis(3-aminopropyl)tetramethyldisiloxane, an acyl chloride compound containing a nitrogen heterocyclic structure, a catalyst and a solvent is reacted to obtain a compound containing a nitrogen heterocyclic structure and a siloxane structure.

4. The preparation method according to claim 3, characterized in that: The acyl chloride compound containing a nitrogen heterocyclic structure is selected from at least one of the structures shown in Formula II-b; 5. The preparation method according to claim 3, characterized in that: The molar ratio of the 1,3-bis(3-aminopropyl)tetramethyldisiloxane to the acyl chloride compound containing a nitrogen heterocyclic structure is 1:2 to 2.5; Preferably, the molar ratio of the 1,3-bis(3-aminopropyl)tetramethyldisiloxane to the catalyst is 1:1 to 3; Preferably, the catalyst is selected from triethylamine and / or pyridine; Preferably, the solvent is selected from at least one of tetrahydrofuran, dimethyl sulfoxide, propylene glycol monomethyl ether and toluene.

6. The preparation method according to claim 3, characterized in that: The preparation method comprises: A mixed solution containing a solvent, a catalyst and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is added dropwise to a solution of an acyl chloride compound containing a nitrogen heterocyclic structure to react and obtain a compound containing a nitrogen heterocyclic structure and a siloxane structure; Preferably, during the dropwise addition, the temperature of the reaction system is controlled to be -10°C to 10°C, and after the dropwise addition is completed, the reaction is continued at 25±2°C for 5 to 8 hours.

7. A photosensitive resin composition, characterized in that: The photosensitive resin composition is obtained by uniformly mixing raw materials containing a polyimide precursor resin, a nitrogen-containing heterocyclic compound and a siloxane structure compound, a photoinitiator, a crosslinking agent, and a solvent I; The nitrogen-containing heterocyclic ring and siloxane structure compound is selected from the nitrogen-containing heterocyclic ring and siloxane structure compound according to any one of claims 1 to 2.

8. The photosensitive resin composition according to claim 7, characterized in that: The mass ratio of the polyimide precursor resin to the nitrogen-containing heterocyclic and siloxane structure compound is 100:0.1-20; Preferably, the mass ratio of the polyimide precursor resin to the photoinitiator is 100:0.1-30; Preferably, the mass ratio of the polyimide precursor resin to the cross-linking agent is 100:0.1-30; Preferably, the mass ratio of the polyimide precursor resin to the solvent I is 100:80-2000.

9. A polyimide film, characterized in that: The polyimide film is obtained by coating and curing the photosensitive resin composition; The photosensitive resin composition is selected from the photosensitive resin composition according to any one of claims 7 to 8.

10. Use of the polyimide film according to claim 9 in semiconductor elements.

Citation Information

Patent Citations

  • Diamine monomer with nitrogen heterocyclic ring and siloxane structure as well as preparation method and application of diamine monomer

    CN117866000A

  • Imidazole silane compound, synthesizing method for the compound, and use thereof

    JP2014028788A

  • Siloxane-containing polyimide coatings for electronic devices

    US4656235A